COLLABORATIVE GOVERNANCE SEBAGAI RESOLUSI KONFLIK SOSIAL DI KABUPATEN SINTANG - Emiliani Nindy Diana Rusega Sim; Laura Apriyan (Universitas Kapuas Sintang, 2025)
Social conflict in Sintang Regency, West Kalimantan, arises from the region’s ethnic, religious,and socio-economic diversity, as well as its complex history of disputes. Notable incidents, includingreligious tensions and land boundary conflicts, underscore the urgency of a systematic approach to conflictresolution. This study aims to analyze the implementation of collaborative governance in addressing socialconflict in Sintang, using three indicators proposed by Ansell and Gash: initial conditions, thecollaborative process, and facilitative leadership. A qualitative descriptive method was employed, involvingfield studies, interviews, observations, and documentation. The findings reveal that synergy among localgovernment— through the National Unity and Political Agency (Kesbangpol), the Community EarlyWarning Forum (FKDM), religious and traditional leaders, and other community stakeholders— plays avital role in facilitating early conflict detection, building mutual trust, and fostering inclusive dialogue.Challenges such as sectoral egos, limited resources, and ineffective communication can be mitigatedthrough active community engagement, the use of information technology, and the enhancement of localleadership capacities. Consequently, collaborative governance proves to be an effective approach forpromoting social stability and harmony in Sintang Regency